Sosialisasi Tentang Pemberdayaan Masyarakat Desa Berbudaya Dalam Meningkatkan Pembelajaran Menuju Desa Unggul (Studi Kasus Desa Gedangsasri, Kab Gunung Kidul) - Maria Atik Sunarti Ekowati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Community service activities through the Community Partnership Program (PKM) Community Empowerment Learning aims to improve the knowledge and skills of cultured village communities in improving learning methods towards superior villages. This activity is in line with the Tri Dharma of higher education and provides learning experiences while working through community empowerment activities in Banaran Village, Playen, Gunung Kidul, Yogyakarta. Judging from the graphic location of the village, it can be used as a potential to develop and provide new knowledge to the community. The target group together with Lecturers and Students carry out PkM activities together. The training activities carried out are the use of computers and teaching training in schools. The results of community service activities through the PKM program have increased community skills in using computers and insight into education.